Psychoeducational Group Assisted with Profession Puppets to Improve Students’ Career Decision Making - Meitasari, Meitasari; Hernisawati, Hernisawati; Maba, Aprezo Pardodi (Kuras Institute, 2019)
Career decision making is very important for individuals. In the adolescent phase, career decision making will play an important role in career development for the future of the individual itself. This study focuses on improving adolescent career decision making by using psychoeducational group services assisted by profession puppet. The purpose of this study was to determine the effectiveness of psychoeducational group assisted with profession puppet media. The method in this study used the Quasi-experiment with Pretest-Posttest Control Group Design. The validity of the instrument uses logical validity while the reliability test uses Alpha Cronbach obtained reliability coefficient on the scale of career decision making value α = 0.877. Data analysis techniques use a t-test comparison of gain scores with confidence interval 95% α = 0.05. This study has a value of Sig.2 (tailed) 0,000 <0,05, therefore it is in accordance with the basis of decision making in the t-test, it can be concluded that Ho is rejected and Ha is accepted, and it means profession puppet within psychoeducational group proved effective to improve student career decision making.